High cardiovascular disease mortality after penile squamous cell carcinomas diagnosis: Results from the United States SEER population, 2005-2016 - Xie, Zequan; Zhan, Xiangpeng; Zheng, Yunwei; Liu, Yang; Chen, Tao; Jiang, Ming; Li, Yu; Fu, Bin (Frontiers in Oncology, 2022)
Background: Cancer survivorship care is an emerging and necessary component of oncology management. To explore cardiovascular disease (CVD)-specific mortality and prognostic factors among patients with penile squamous cell carcinomas (PSCC). These results aid clinicians in furtherly understand this disease's prognosis. Method: We analyzed Surveillance, Epidemiology and End Results Program data for 5215 PSCC cases diagnosed between 1975 to 2016. We calculated standardized mortality ratios (SMRs) of CVD and all-cause mortality, comparing PSCC patients with general population men. A cumulative mortality curve and competitive risk regression model were utilized to evaluate the prognostic factors of CVD-specific death. Results: Death distribution is as follows: PSCC (30.5%), CVD (25.5%), other cancers (19.3%), and other causes (24.6%). PSCC patients are more like to die from CVD (SMR=21.02, 95%CI: 18.35-23.7) and all-cause death compared with the general population. In the competitive risk model, higher CVD mortality is associated with older age, region, year of diagnosis, stage, and receiving surgery. Patients with localized stage show a higher risk of CVD-specific death than those with regional or distant. Meanwhile, the risks of CVD-specific death are higher in patients with surgery than those without. Conclusion: Our study mainly reveals that PSCC itself or undergoing surgery would lead to a higher risk of death from cardiovascular disease. In the future, more work in educating health care professionals on the components of survivorship care is needed to meet the long-term and late effects cancer patients experience.